Association between cholesterol gallstones and testosterone replacement therapy in a patient with primary hypogonadism - S. Squarza; U.G. Rossi; P. Torcia; M. Cariati (Revista de Gastroenterología de México (English Edition), 2018)
A 16-year-old boy had a past medical history of primary hypogonadism, due to bilateral anorchia. He presented with gallstones located in the gallbladder and a mild dilatation of the intrahepatic biliary tree. The histology study reported cholesterol gallstones. The patient had been treated with testosterone replacement therapy since infancy. We suggest a possible correlation between testosterone replacement therapy and the presence of cholesterol gallstones. Resumen: Tratamos a un niño de 16 años de edad con hipogonadismo primario debido a la anorquia bilateral, que presentó cálculos biliares en la vesícula biliar con una leve dilatación del árbol biliar intrahepático. La histología de los cálculos biliares confirmó la naturaleza de colesterol de los mismos. El niño fue tratado desde la infancia con terapia de reemplazo de testosterona. Sugerimos una posible correlación entre la terapia de reemplazo de testosterona y la presencia de cálculos biliares de colesterol. Keywords: Gallstones, Testosterone, Cholesterol, Primary hypogonadism, Therapy, Gallbladder, Palabras clave: Cálculos biliares, Testosterona, Colesterol, Hipogonadismo primario, Terapia, Vesícula biliar